Linearly Polarized γ Photon Generation from Unpolarized Electron Bunch Interacting with Laser - Yang He; Burabigul Yakup; Mamat Ali Bake (Applied Sciences)
Highly polarized high-energy <semantics>γ</semantics> photons demonstrate potential application in the efficient detection of strong-field quantum electrodynamics effects. Currently, polarized <semantics>γ</semantics>-rays are mostly generated in conventional particle accelerators, which are typically huge and expensive. This study proposes a scheme for generating linearly polarized <semantics>γ</semantics> photons from the interaction of a GeV-level unpolarized electron bunch with currently available laser pulses at moderate intensity. We investigate the scheme by considering the electron bunch of various initial energies and various laser intensities using two-dimensional particle-in-cell simulation and the theory of quantum electrodynamics. Results show that GeV-level linearly polarized <semantics>γ</semantics> photons were generated from the interaction with a high polarization degree of <semantics>63%</semantics> and brightness of <semantics>1.8×1021<mspace width="3.33333pt"></mspace>photons/(s<mspace width="3.33333pt"></mspace>mm2<mspace width="3.33333pt"></mspace>mrad2<mspace width="3.33333pt"></mspace>0.1<mspace width="3.33333pt"></mspace>%<mspace width="3.33333pt"></mspace><mspace width="4pt"></mspace>bandwidth(BW))</semantics> at 1 GeV. Moreover, it is also shown that the photon generation rate was enhanced with higher laser intensity and electron bunch energy, whereas the polarization degree decreased with higher laser intensities. Our scheme can be realized experimentally at currently available laser wakefield electron acceleration facilities.